Adenosine Deaminase in Pleural Effusion and Its Relationship with Clinical Parameters in Patients with Malignant Pleural Mesothelioma. (2nd July 2020) - Nakajima, Yasuhiro; Kuribayashi, Kozo; Ishigaki, Hirotoshi; Tada, Akio; Negi, Yoshiki; Minami, Toshiyuki; Takahashi, Ryo; Doi, Hiroshi; Kitajima, Kazuhiro; Yokoi, Takashi; Kijima, Takashi
Abstract: Pleural effusion adenosine deaminase (ADA) levels are elevated in various diseases. We investigated whether pleural effusion ADA levels differ among patients with malignant pleural mesothelioma (MPM), lung cancer (LC), and benign diseases, including tuberculous pleurisy. We examined 329 patients from February 2002 to July 2013. There were 131 MPM cases with ADA levels of 32.29 IU/L; 117 LC cases with ADA levels of 21.12 IU/L; 54 benign disease cases with ADA levels of 20.98 IU/L. A significant difference existed in pleural effusion ADA levels between MPM and benign disease patients. Pleural effusion ADA levels were significantly higher in MPM patients.